Interferometric probes of ultrarelativistic nuclear collisions - Padula, Sandra S. [UNESP]; Gyulassy, Miklos (My University, 1991)
We suggest that pion and kaon interlerometry are complementary probes that help differentiate hadronic resonance gas from plasma dynamical models. We also discuss how interferometry could be used to test the presence of resonances at AGS energies. Finally, we study the A dependence of interferometry in the resonance model at 200 A GeV. © 1991.